The humanities between global integration and cultural diversity - Mersmann, Birgit; Kippenberg, Hans Gerhard; Gurrey, Owen; Bachmann-Medick, Doris; Dogramaci, Burcu; Haschemi Yekani, Elahe (Concepts for the study of culture, 2016)
Modernization and digital globalization have proven to mark major thresholds where paradigmatic shifts and realignments take place. This volume aims to capture the reconfiguration of humanistic study between the forces of global integration and cultural diversification from a full range of disciplines within the humanities and social sciences. The key issue is discussed in three major parts. The first chapter examines transnational interpolations of the humanities as potential indicator for a globalizing humanistic research. The second chapter deals with humanistic revisions of modernity with and against globality. The third chapter discusses the ambiguous constitution of cultural diversity as a complement and counter-movement to global integration, ideologically moving between social cohesion and exclusion. The final chapter outlines what the threshold-crossing from modern to global humanities will mean for the future of humanistic research.The multidisciplinary study of culture within the history of the humanities documents and reflects the mobility and migration of its concepts and methods, moving and translating between disciplines, research traditions, historical periods, academic institutions, and the public sphere.